2022
DOI: 10.3389/fonc.2022.927640
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of RNA N6-Methyladenosine Modification in Pancreatic Cancer

Abstract: Pancreatic cancer (PC) is one of the most common malignant cancers, ranking the seventh highest causes of cancer-related deaths globally. Recently, RNA N6-methyladenosine (m6A) is emerging as one of the most abundant RNA modifications in eukaryote cells, involved in multiple RNA processes including RNA translocation, alternative splicing, maturation, stability, and degradation. As reported, m6A was dynamically and reversibly regulated by its “writers”, “erasers”, and “readers”, Increasing evidence has revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 183 publications
0
2
0
Order By: Relevance
“…Three RNA-seq datasets GSE16561 (n = 63) 53 , GSE102541 (n = 9) 54 , and GSE140275 55 (n = 6) were downloaded from the Gene Expression Omnibus (GEO) database ( https://www.ncbi.nlm.nih.gov/gds/ ). GSE16561 was used as the training set which included 39 cases of IS samples and 24 of normal samples.…”
Section: Methodsmentioning
confidence: 99%
“…Three RNA-seq datasets GSE16561 (n = 63) 53 , GSE102541 (n = 9) 54 , and GSE140275 55 (n = 6) were downloaded from the Gene Expression Omnibus (GEO) database ( https://www.ncbi.nlm.nih.gov/gds/ ). GSE16561 was used as the training set which included 39 cases of IS samples and 24 of normal samples.…”
Section: Methodsmentioning
confidence: 99%
“…Abnormal m6A modification of lncRNA is currently found in PC tissues and cell lines (Fig. 3 ) [ 137 , 138 ]. Chen et al found that METTL14-modified LncRNA LIFR-AS1 promotes the progression of PC.…”
Section: Functions Of Lncrna-rna Modification In Different Types Of C...mentioning
confidence: 99%